KUALITAS PELAYANAN ADMINISTRASI BALIK NAMA BERDASARKAN JUAL BELI DI KANTOR PERTANAHAN KABUPATEN SIGI - Prabandari, Retno; Pasinringi, Andi; Nurhannis, Nurhannis (Katalogis, 2019)
The purpose of this study was to determine the quality of administrative services behind the name based on buying and selling at the Sigi Regency Land Office. This research uses descriptive qualitative type, with the number of informants involved as many as 7 informants through Purposive Sampling techniques. In addition, in the data collection technique in this study through observation, interviews and documentation. With the method of data analysis through (1) data reduction, (2) data display, and (3) conclusion and verification. From the results of the study, it is known that the quality of administrative services behind the name based on buying and selling at the Sigi Regency Land Office is considered to be running poorly, this is based on the results of research that shows that two of the four aspects referred to in this study are still not good These are speed and convenience, where in the service process the administration of the name based on buying and selling is quite time consuming, where in the service process it still takes between fifteen to twenty days, whereas in the standard of service the time needed in the service process the administration of returning the name based on buying and selling only takes between five to seven days. In addition, in its service, the Sigi Regency Land Office still applies a fairly complex service process, and also the many service requirements that are considered rather difficult for the people who need the service.